2020
DOI: 10.1038/s41586-020-1936-2
|View full text |Cite|
|
Sign up to set email alerts
|

Targeting of temperate phages drives loss of type I CRISPR–Cas systems

Abstract: Upon infection of their host, temperate phages (viruses that infect bacteria) enter either a lytic or a lysogenic cycle. The former results in bacterial cell lysis and phage release (horizontal transmission), while lysogeny is characterized by integration of the phage in the host genome and dormancy (vertical transmission) 1. Co-culture experiments of bacteria and temperate phage mutants, which are locked in the lytic cycle, have shown that CRISPR-Cas can efficiently Users may view, print, copy, and download t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
87
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(93 citation statements)
references
References 35 publications
(57 reference statements)
4
87
2
Order By: Relevance
“…For each host defense system microbes have evolved, however, viruses appear to have developed a countermeasure, such as the anti-restriction, anti-CRISPR and anti-toxin systems (Dolgin, 2019;Rollie et al, 2020). While these viral countermeasure systems have been largely described for genera not normally found in the rumen, for example, Pseudomonas and Mycobacterium (Dedrick et al, 2017;Landsberger et al, 2018).…”
Section: Maintenance Of Microbial Diversitymentioning
confidence: 99%
“…For each host defense system microbes have evolved, however, viruses appear to have developed a countermeasure, such as the anti-restriction, anti-CRISPR and anti-toxin systems (Dolgin, 2019;Rollie et al, 2020). While these viral countermeasure systems have been largely described for genera not normally found in the rumen, for example, Pseudomonas and Mycobacterium (Dedrick et al, 2017;Landsberger et al, 2018).…”
Section: Maintenance Of Microbial Diversitymentioning
confidence: 99%
“…It has been suggested that following the integration of an STS, the CRISPR-Cas system must become inactivated in order to survive, and that this phenomenon could explain the abundance of highly degraded CRISPR systems that contain cas pseudogenes (12). Recent experimental evolution studies have shown that large genomic deletions encompassing the entire CRISPR-Cas locus can occur as a consequence of auto-immunity to prophages (35).…”
Section: Self-targeting Spacers (Sts) Are Often Found In Crispr-encodmentioning
confidence: 99%
“…Bacteria that express acrs can tolerate "self-targeting" spacers that, in the absence of CRISPR-Cas inhibition, would otherwise cause lethal genomic cleavage (Bondy-Denomy et al, 2013;Vercoe et al, 2013;Xu et al, 2019;Rollie et al, 2020). The presence of these selftargeting spacers can therefore be used to identify bacterial genomes that likely encode anti-CRISPR proteins capable of inhibiting their endogenous CRISPR system (Rauch et al, 2017;Marino et al, 2018;Watters et al, 2018Watters et al, , 2020.…”
Section: Resultsmentioning
confidence: 99%